EXPLORING BRAND AWARENESS AND UTILIZATION PATTERNS OF POISON CONTROL CENTER SERVICES IN THAILAND: A COMPARATIVE STUDY AMONG HEALTHCARE PROFESSIONALS AND THE GENERAL PUBLIC - Suengkamolpisut, Wallapa; Sud-On, Ploy; Mekavuthikul, Pattaraporn (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2024)
Purpose – The purpose of this study is to compare the brand awareness and utilization patterns of Poison Control Center services in Thailand among healthcare professionals and the general public. Methodology – This study employs quantitative methodology to compare the brand awareness and utilization patterns of Poison Control Center services among healthcare professionals and the general public in Thailand. Results – The results of the study reveal that healthcare professionals in Thailand have significantly higher brand awareness of Poison Control Center services compared to the general public. The findings also indicate that healthcare professionals are more likely to utilize these services than the general public. Implications – Implications of this study suggest the need for targeted educational campaigns to increase brand awareness and encourage more effective utilization of Poison Control Center services among the general public in Thailand. Originality/Value – This study contributes to the existing literature by examining the brand awareness and utilization patterns of Poison Control Center services in Thailand, specifically comparing healthcare professionals and the general public. The findings highlight the need for targeted educational campaigns to increase brand awareness and promote the effective utilization of Poison Control Center services among the general public in Thailand. The findings of this study highlight the disparity in brand awareness and utilization of Poison Control Center services between healthcare professionals and the general public in Thailand.